Women and Politics: Movement and Militance of “EMak-Emak” and “Srikandi” in the General Election 2019 - Heri Junaidi; Chici Rima Putri Pratama (Jurnal Studi Sosial dan Politik, 2021)
This article is a scientific account of the results of a study entitled Women and Politics: The Movement and Militance of “EMak-Emak” and “Srikandi” in the General Election 2019. The background of the research problem is assessed from the role of women still in the category of the domestic realm, and still leaves a negative assessment of women who carry out activities in the public sphere, including active participation in politics. This type of research used a qualitative research type, namely research procedures that produce descriptive data. Sources of data obtained are primary data and secondary data. The method of data collection was done through interviews and a thorough literature review. The data analysis technique used is a qualitative analysis technique which is then presented descriptively. As for the conceptual and theoretical framework that is in use is the theory used in answering it uses Michel Foucault's discourse theory and the theory of the movement of women. The results of the study concluded that the women's movement in Indonesia in the 2019 elections which were members of the " Emak-Emak" and the “Srikandi” Group had various reasons, namely as evidence of the identity of the women's political participation movement. The characteristics of the women's movement are generally coordinated with a clearly measurable agenda and steps. The impact of this movement changed the mindset of Indonesian society that women are not only in the reproductive but also shows that they are also capable of entering the productive sphere, including the political sphere.